2016
DOI: 10.5194/aab-59-435-2016
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of morphological and meristic traits and their variations between two different populations (wild and cultured) of <i>Cichlasoma festae</i>, a species native to tropical Ecuadorian rivers

Abstract: Abstract. This study was carried out to determine morphometric and meristic characteristics of two populations (wild and cultured) of Cichlasoma festae and to establish whether populations could be discriminated based on morphometric variability. Twenty-two morphometric and four meristic characters were used to test the hypothesis differentiation. Univariate analysis of variance (ANOVA) from 100 adult specimens showed significant differences (p < 0.05) for 21 standardized morphometric measurements out of 26 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
38
4
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 28 publications
(35 reference statements)
8
38
4
4
Order By: Relevance
“…In the current study, only 2 morphometric parameters (DFRL and P3) differ between populations. In contrast, several authors (Solomon et al, 2015;González et al, 2016) found significant differences between natural and domesticated fish populations. Besides, a few of the registered meristic characters (PcFR and RPcF) showed significant differences between populations, similar to the findings of Solomon et al (2015).…”
Section: Morphometric and Meristic Charactersmentioning
confidence: 87%
“…In the current study, only 2 morphometric parameters (DFRL and P3) differ between populations. In contrast, several authors (Solomon et al, 2015;González et al, 2016) found significant differences between natural and domesticated fish populations. Besides, a few of the registered meristic characters (PcFR and RPcF) showed significant differences between populations, similar to the findings of Solomon et al (2015).…”
Section: Morphometric and Meristic Charactersmentioning
confidence: 87%
“…Although comparisons of the morphology between cultured and wild fishes from several species have already been carried out by several authors (Solomon et al, 2015;González et al, 2016), differences based on nutritional composition among cultured and wild C. festae stocks, have not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…Los animales crecen de modo progresivo con diferencias significativas entre controles (p<0,05) y manteniendo en los pesos finales bajo error estándar y muy bajo coeficiente de variación. Con la tecnología Biofloc se obtuvieron crecimientos superiores a los reportados por Rodríguez et al (2017) (2) y González et al (2016) (14) para la misma especie en sistemas con recirculación de agua. Los pesos finales no se ajustaron a una distribución normal (p<0,05).…”
Section: Resultados Y Discusiónunclassified